Gugon Tuhon for Javanese Women to Promote Character Building: A Pragmatic Perspective - nurjanah, komariyah; widhyasmaramurti, widhyasmaramurti (State institute of islamic studies salatiga, 2020)
Gugon tuhon (GT) is one of the Javanese sayings or oral traditions that contains piwulang ‘knowledge’ as guidance in conducting polite behaviors that generally in the forms of orders and prohibitions. GT contains frightening elements so that they are not violated by those who believe them. GT has much guidance that relates to humans’ life, and one of them is GT for Javanese women to behave well in order to have good characters. GT data that are used in this research were taken from a text entitled Serat Gugontuhon Prawira Winarsa on www.sastra.org that focused on appropriate behaviors for Javanese women. In the Javanese community, GT is generally acquired through informal oral interaction. Therefore, understanding the pragmatic meaning is necessary. However, the data which were taken from written text raised a problem, namely what the pragmatic meanings of GT for Javanese women are. This research aims in explaining the meanings of GT for Javanese women that can promote character building. Then, in order to obtain more detailed pragmatic meanings’ results, interviews with mothers and daughters were also conducted in Sambiresik Village, Kediri. This research used the qualitative method and Austin's speech action theory (1984) which consisted of locutions, illocutions, and perlocutions acts meaning. The results showed that the meaning of locutions and illocutions are in the form of guidance to avoid prohibitions. So the Javanese women would perform well-mannered behaviors that according with the common norm. The perlocutions’ meanings were more as a suggestion act in order to avoid the prohibitions. Although the meanings of GT are still understood by mothers and some daughters, yet they believed that some of the guidance is not relatable to the present condition due to the enhancement of technology. GT which are not in accordance with present times are no longer heard in the community. It leads to a threat of the GT extinction in the future. Therefore, this research is expected to be an effort in preserving Javanese language and culture through GT because GT is known as Javanese local wisdom that is not simply as a belief but also has elements of truth that are useful to human’s life. Keywords: Javanese language, gugon tuhon, pragmatic, women's characters